Communication Barriers in Speaking: Challenges Faced by Indonesian EFL Learners - Nazri, M. Adib (Journal of English Language and Education, 2025)
Speaking is widely acknowledged as one of the most complex language skills to acquire, particularly in the context of global interaction. Within the framework of Indonesia’s independent curriculum policy, the implementation of English presents considerable challenges, as many learners struggle to utilize the language effectively for communication. This study employed a qualitative descriptive approach to investigate the difficulties encountered by learners of English as a foreign language. The participants consisted of 120 first-year students enrolled in the English Education Study Program at Hamzanwadi University, distributed across four classes. Data collection involved students' self-recorded speaking videos and questionnaire responses. The findings reveal three predominant challenges: grammatical errors (50%), pronunciation difficulties (25%), and limited vocabulary (15%), with additional factors constituting less than 5%. These results aim to enhance understanding of speaking proficiency barriers in EFL contexts and offer practical recommendations for educators and curriculum developers seeking to improve instructional strategies and learner outcomes.